Spread of Coronavirus 2019 From Wuhan to Rural Villages in the Hubei Province - You, Maolin (Open Forum Infect Dis, 2020)
BACKGROUND: This study aimed to describe the spread of coronavirus disease 2019 (COVID-19) from Wuhan to rural villages in the Hubei Province. METHODS: The analysis revealed the following: (1) COVID-19 spread from Wuhan to other cities and rural areas in Hubei, but the disease did not become widespread in rural villages because of strict prevention measures and urbanization; (2) according to the fluctuation in the number of confirmed cases reported in Hubei after January 23, 2020, we inferred that the infected patients on the same day will become ill during the next 20 days; (3) the advanced traffic system facilitates the direct spread of COVID-19 from Wuhan to counties, towns, and villages in the Hubei Province. RESULTS: There is a low possibility of COVID-19 spread from prefecture-level cities to rural areas. CONCLUSIONS: The findings imply that the government should limit the travelers from the cities to the rural areas, pay more attention to the prevention and control of severe acute respiratory syndrome coronavirus 2 in cities, and appropriately prolong the isolated observation period of travelers.